The significance of political conviction - Alvydas Jokubaitis (Politologija)
The perception of the significance ascribed to political conviction fluctuates between two extremes, namely exaggerated individualism preached by J.S. Mill and the processual thinking advocated by G. Hegel. The followers of the first author are convinced that an individual should be treated as the final source of social norms, whereas those supporting Hegel (and accordingly F. Nietzsche) tend to think that the genuine source generating social meanings is a certain power superior to an individual. It could be a system, a discourse, a structure, or some process.